THE GROWTH OF FOREIGN INVESTMENT IN SERBIA - THE LAW AND WHAT ELSE? - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Abstract: Foreign direct investment may represent a channel for reducing the lag behind the developed countries in the area of research, development, marketing and managerial skills. To avoid possible negative consequences of foreign investments it is necessary to create such a business climate that will provide incentives that research results realized in Serbia find their use in the industry of Serbia. By a series of criteria that foreign investors take into consideration when deciding where, how, and what to invest Serbia has a very bad place. Emigration of highly educated young professionals that has lasted for more than twenty years deteriorates competitive position of Serbia. The middle class is the basis for stability and development for every country. International institutions considered that the business climate in Serbia is basically bad. It must be changed. One of the important steps in this direction could be the adoption of the new law on investments. But the law itself is not sufficient.